Effective Communication in the Workplace from the Perspective of the Qur'an - Anjas; Mohammad Fattah Fattah (UIN Kiai Haji Achmad Siddiq Jember, 2026)
Workplace communication failures increasingly emerge as a critical challenge in modern professional environments, often stemming from the absence of ethical and values-based communication frameworks. This study examines the concept of effective communication in the workplace as reflected in QS. Al-Qashash verses 26–28, through a comparative analysis of two prominent Indonesian Quranic exegeses: Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Misbah by M. Quraish Shihab. The research aims to identify the principles of effective workplace communication according to both exegetes and to explore their similarities and differences. A qualitative library research method was employed, utilizing content analysis, descriptive analysis, and comparative analysis of primary and secondary sources. The findings reveal that both exegetes agree on two foundational pillars of effective workplace communication: professional competence (al-qawiyy) and moral integrity (al-amīn), alongside the necessity of transparent, unambiguous, and non-coercive work contracts, with Allah as the spiritual witness of every agreement. However, they differ in approach: Hamka employs an ethical-narrative method that extracts moral values chronologically from the Quranic narrative, emphasizing character and humanity, while Quraish Shihab adopts a linguistic-contextual approach that systematically analyzes Quranic diction to derive operational communication principles with stronger emphasis on workers' rights protection. These two approaches are complementary, together forming a comprehensive Quranic communication model that is simultaneously ethical, rational, transparent, and spiritually accountable.